Cover Feature: Stable High‐Pressure Methane Dry Reforming Under Excess of CO2 (ChemCatChem 23/2020). Issue 23 (9th November 2020) - Ramirez, Adrian; Lee, Kunho; Harale, Aadesh; Gevers, Lieven; Telalovic, Selvedin; Al Solami, Bandar; Gascon, Jorge
Abstract : The Cover Feature shows the potential of dry reforming in the recycling of carbon dioxide. In their Full Paper, A. Ramirez et al. demonstrate that coke deposition during methane dry reforming at high pressures can be avoided by using sub‐stoichiometric CH4 :CO2 ratios, improving in this way not only catalyst stability but also the amount of CO2 abated. More information can be found in the Full Paper by A. Ramirez et al.